Locating postcolonial narrative genres - Goebel, Walter; Schabio, Saskia (Routledge research in postcolonial literatures ;, 2013)
This volume explores how postcolonial texts have determined the evolution or emergence of specific formal innovations in narrative genres. While the prominence of questions of cultural identity in postcolonial studies has prevented due attention to concerns of literary form and aesthetics, this book gives premium to the literary, aiming to delineate the evolution of specific narrative techniques as part of an emerging postcolonial aesthetics. Essays delineate elements of an emergent postcolonial narratology across a variety of seminal generic forms, such as the epic, the novel, the short st.